Case Report: A case series of using ultrasound-guided continuous parasacral ischial plane blocks to promote ulcer healing and pain relief in people with diabetic foot ulcers - Ye, Peng; Pan, Xuan; Zhuang, Jing; Fan, Hanliang; Zheng, Xiaochun; Zheng, Ting (Frontiers in Endocrinology, 2025)
BackgroundDiabetic foot ulcers (DFU) are a prevalent complication of diabetes, leading to significant morbidity, mortality, and amputation rates. Chronic non-healing DFU often result from peripheral neuropathy, microvascular issues, and infection, with poor blood and oxygen supply being critical factors in delayed healing. The development of new treatments to promote blood supply and accelerate ulcer healing is a significant area of research for DFU management.MethodsIn this case series, nine patients with chronic diabetic ulcers received ultrasound-guided continuous parasacral ischial plane block (CPIPB) for 2 weeks, combined with standard care (SOC) for 12 weeks. Our objective was to assess the reduction in wound size and the rate of complete healing 12 weeks after the start of treatment.ResultsAmong the nine patients, six achieved complete healing of their diabetic foot ulcers, while the remaining three showed significant improvement with more than a 50% reduction in the initial ulcer area. This approach not only provided analgesia but also increased foot skin temperature and blood supply in the lower limb arteries, potentially promoting angiogenesis and revascularization. Local anesthetic leakage at the catheter insertion site occurred in two cases during CPIPB.ConclusionCPIPB can promotes diabetic foot ulcer healing while providing effective analgesia in the lower limbs. This approach may offer a valuable complement to conventional treatments, particularly for patients with severe pain.